2020
DOI: 10.1016/j.jcv.2020.104539
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of Abbott ARCHITECT SARS-CoV-2 IgG immunoassay in comparison with indirect immunofluorescence and virus microneutralization test

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 6 publications
9
81
1
Order By: Relevance
“…Our results seem comparable to previous studies in which the CLA test that we used showed a sensitivity and specificity close to 100% when compared with PCR +/samples [23][24][25], while the LFA [26] and the ELFA [17] appear to be less sensitive and (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Our results seem comparable to previous studies in which the CLA test that we used showed a sensitivity and specificity close to 100% when compared with PCR +/samples [23][24][25], while the LFA [26] and the ELFA [17] appear to be less sensitive and (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Assays to detect nAbs are technically challenging and not routinely performed by clinical laboratories, however the need to determine the nAb titer as part of vaccine clinical trials and initially in convalescent plasma donors prior to transfusion necessitated the availability of such assays; whether the S/Co ratio provided by commercially available assays correlate to nAb levels is yet to be determined. Additionally, as semiquantitative and quantitative antibody assays come to market, correlation between reported values and neutralizing antibody levels will also be important to establish (13)(14)(15).…”
Section: Interpretation Of Serologic Test Resultsmentioning
confidence: 99%
“…In contrast, the indirect immunofluorescence assay had sensitivities of 58.3%, 85.7%, and 100% at 7, 14, and >14 days, respectively. 25 The study suggests that indirect immunofluorescence assays may be better for detecting SARS-CoV-2 antigens or antibodies at the early stages of infection compared to the Abbott Architect SARS-CoV-2 IgG immunoassay. An Italian study also assessed the sensitivity and specificity of the LIAISON SARS-CoV-2 S1/S2 IgG assay using 1500 clinical samples.…”
Section: Italian Antibody Studiesmentioning
confidence: 90%
“…An Italian study compared the Abbott Architect SARS-CoV-2 IgG immunoassay to an indirect immunofluorescence assay and a neutralization assay from COVID-19 samples collected at different times from symptom onset. 25 The sensitivities of the Abbott Architect SARS-CoV-2 IgG immunoassay at 7, 14, and >14 days were 8.3%, 61.9%, and 100%, respectively. In contrast, the indirect immunofluorescence assay had sensitivities of 58.3%, 85.7%, and 100% at 7, 14, and >14 days, respectively.…”
Section: Italian Antibody Studiesmentioning
confidence: 94%